2017
DOI: 10.1002/ecy.2008
|View full text |Cite
|
Sign up to set email alerts
|

Influence of neighboring plants on the dynamics of an ant–acacia protection mutualism

Abstract: Ant-plant protection symbioses, in which plants provide food and/or shelter for ants in exchange for protection from herbivory, are model systems for understanding the ecology of mutualism. While interactions between ants, host plants, and herbivores have been intensively studied, we know little about how plant-plant interactions influence the dynamics of these mutualisms, despite strong evidence that plants compete for resources, that hosting ants can be costly, and that host-plant provisioning to ants can th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 73 publications
1
12
0
Order By: Relevance
“…Because P. megacephala does not induce nectar production on A. drepanolobium , its invasion also is likely to indirectly facilitate T. penzigi by generating a landscape of low‐reward host plants, a process that may “screen” out the more energetically demanding, nectar‐dependent Crematogaster mutualists (see Archetti et al 2011, Heil 2013). Our experimental manipulation of host plant nectaries showed that establishment success was higher for T. penzigi queens and lower for Crematogaster queens on low‐reward host plants, consistent with a prior study demonstrating greater persistence of T. penzigi vs. C. mimosae colonies on saplings with lower reward levels (Palmer et al 2017). Coupled with the recruitment limitation we observed for Crematogaster spp.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Because P. megacephala does not induce nectar production on A. drepanolobium , its invasion also is likely to indirectly facilitate T. penzigi by generating a landscape of low‐reward host plants, a process that may “screen” out the more energetically demanding, nectar‐dependent Crematogaster mutualists (see Archetti et al 2011, Heil 2013). Our experimental manipulation of host plant nectaries showed that establishment success was higher for T. penzigi queens and lower for Crematogaster queens on low‐reward host plants, consistent with a prior study demonstrating greater persistence of T. penzigi vs. C. mimosae colonies on saplings with lower reward levels (Palmer et al 2017). Coupled with the recruitment limitation we observed for Crematogaster spp.…”
Section: Discussionsupporting
confidence: 90%
“…“stress tolerance” traits including T. penzigi ’s lower dependence on host plant nectar (Palmer et al 2002, 2017), and avoidance and escape behaviors allow for longer persistence times on host plants, allowing colonies to reach reproductive maturity. Although C. nigriceps is also a strong colonist (Stanton et al 2002), its strong dependence on host plant nectar and high levels of interspecific aggression (Palmer 2004) likely underlie its inability to persist within invaded habitats.…”
Section: Discussionmentioning
confidence: 99%
“…new unlignified spines), compounded by the low concentrations of polyphenolics and tannins in young A. drepanolobium leaves (Rubanza et al., ), though an extensive diet study (in unburned habitat) found no evidence that cattle consume A. drepanolobium (Odadi et al., ). We suggest several other potential reasons that cattle did not increase tree height as we had expected, and may instead have reduced it: (a) by reducing grass cover, cattle may have increased the apparency of resprouts to wild ungulate browsers (Riginos & Young, ), in particular steenbok, which are small browsers that have access to all KLEE plots; (b) grass reduction by cattle may have indirectly increased stress from the physical environment, for example, by increasing evaporative demand (Maestre, Bautista, & Cortina, ; Palmer et al., ); or (c) cattle may have trampled resprouting tree tissues (Cumming & Cumming, ).…”
Section: Discussionmentioning
confidence: 70%
“…The result suggests that a higher population density and genetic diversity within plant populations favor the establishment of ant–plant protective mutualisms. Although I only focused on intraspecific competition, further investigations on interspecific competition may also contribute to gaining a better understanding of the ant–plant protective mutualisms (Palmer et al, 2017). Accordingly, the findings of this study highlight the need to take into consideration plant–plant interactions when investigating ant–plant mutualisms.…”
Section: Discussionmentioning
confidence: 99%